Selenium influences mmu-miR-155 to inhibit inflammation in Staphylococcus aureus-induced mastitis in mice. Issue 10 (23rd September 2019) - Zhang, Zhen-biao; Guo, Ying-fang; Li, Cheng-ye; Qiu, Chang-wei; Guo, Meng-yao
Abstract : Mastitis, a major disease affecting dairy cows, is most commonly caused by Staphylococcus aureus ( S. aureus ). Abstract : Mastitis, a major disease affecting dairy cows, is most commonly caused by Staphylococcus aureus ( S. aureus ). Selenium (Se) can activate pivotal proteins in immune responses and regulate the immune system, and microRNA-155 (miR-155) is a key transcriptional regulator for inflammation-related diseases. We constructed the model of mouse mastitis in vivo and primary mouse mammary epithelial cells (MMECs) in vitro, which were induced by S. aureus . Se content of the mammary was estimated using an atomic fluorescence spectrophotometer. Histopathological analysis was performed via hematoxylin and eosin (H&E) staining. The mmu-miR-155-5p mimic was transfected in MMECs, and viability was determined through the MTT assay. Transfected efficiency was evaluated by qPCR and fluorescence staining. Cytokines including TNF-α, IL-1β, IL-10 and TLRs were detected with qPCR. In addition, western blotting was used to evaluate the expression of the NF-κB and MAPKs signaling pathways. The results demonstrated that a Se-supplemented diet improved the content of Se in mammary tissues. Histopathological studies indicated that the mammary glands were protected in the Se-supplemented group after S. aureus infection. Se-supplementation suppressed the production of MPO, mmu-miR-155, TNF-α, IL-1β, and TLR2 and significantly inhibited the phosphorylation of NF-κB and MAPKs in vivo and in vitro . All the data indicated that mmu-miR-155 played a pro-inflammatory role in our study, and Se-supplementation could suppress the expression of mmu-miR-155 to inhibit inflammation in S. aureus -induced mastitis in mice.